Manajemen Solvabilitas dan Kesehatan Keuangan Perusahaan, Studi Kasus: PT Gudang Garam, Tbk - Imaduddin, Muhamad; Hidayat, Ari; Kamil, Musthofa; Sobana, Dadang Husen (BISMA : Business and Management Journal, 2025)
Solvency management is an important aspect of corporate financial management, especially in ensuring the company's ability to meet its long-term obligations. This study analyzes the solvency of PT Gudang Garam by reviewing the capital structure through Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR) from 2019 to 2023. The analysis results show that PT Gudang Garam managed the proportion of debt and equity well. DER decreased significantly in 2020, reflecting an improved capital structure, although there were still controlled fluctuations in the following years. DAR also showed stability, reflecting the company's financial balance. For comparison, this study compares PT Gudang Garam's solvency with similar companies, such as PT HM Sampoerna, to provide a broader context. The study also adds data visualization to clarify solvency trends and offers strategic recommendations to improve financial stability.